Adoption of solar photovoltaic systems in households: Evidence from Uganda. (20th December 2021) - Aarakit, Sylvia M.; Ntayi, Joseph M.; Wasswa, Francis; Adaramola, Muyiwa S.; Ssennono, Vincent F.
Abstract: With over 70% of households without access to clean energy, Uganda presents a huge potential for increased adoption of solar photovoltaic (PV) technologies. However, their uptake is relatively low. This study employs a nationally representative data set from Uganda's National Electrification Survey of 2018 to analyze factors influencing households' choice of solar PV system. Conditional mixed process model was estimated for quantification of associations between flexible payment mechanism, influential persons, access to grid electricity and solar PV adoption in the first stage, then type of solar PV adopted in the second stage. We find that, the determinants of adoption as well as type of solar PV adopted are heterogeneous. Specifically, flexible payment mechanism is positive for uptake of solar home systems and solar kit; Influential people were insignificant in all cases, while grid access was negatively associated with uptake of both solar kits and solar home systems. We further find that, rural residence, income, type of house are significant drivers of solar PV type adopted. Conversely, education attainment was positive and significantly associated with adoption but insignificant for type of solar PV adopted. Sex of household head was significant for uptake of solar kit. Our findings suggest that, solar PV uptake is a rural phenomenon and affordability is the main driver of solar PV type adopted. Flexible payment mechanism enhances the ability of income constrained households to afford relatively expensive solar PV systems. Hence, any policy interventions geared at scaling uptake of solar home systems should address affordability. Solar companies should continue to offer flexible payment modalities and target rural household. Highlights: Drivers for adoption solar photovoltaic (PV) devices in Uganda are examined. Conditional mixed process model is used as main analysis tool in this study. Flexible payment mechanism rises chance of households adopting solar home systems. Solar PV devices adoption is largely a rural phenomenon in Uganda. Policy intervention should focus on addressing affordability issues in rural areas.